Entrepreneurship Practices as Business Optimization and Empowerment of Creative Human Resources Among Students - Arimbi Sekar Arum; Dita Kusuma Anggraini; Widagdo Widagdo; Muchhamad Sholeh; Sunjoyo Sunjoyo; Satrio Sakti Rumpoko; Zandra Dwanita Widodo (Lembaga Pengembangan Kinerja Dosen, 2024)
Social media is a tool for interacting between individuals with one another. The use of social media in Indonesia is very massive. However, this use is only used for communicative purposes, not to reach a wider reach in product marketing. Social media can be used for product promotion. The explanation above has explained the importance of use. Therefore, this service is carried out in order to provide an understanding of the importance of using social media for MSMEs. Many MSMEs still do not understand the importance of promotion via social media, either through personal company accounts or through people who promote their products. So we conducted outreach to MSMEs on optimizing the use of social media, by assisting in creating an Instagram account and how to use Instagram to maximize promotion at the Rica-rica Mbok Usreg food stall located in Ngemplak, Boyolali. Socialization of the use of social media to Mbok Usreg food stalls uses quantitative methods by conducting field surveys and also collecting data after the survey is carried out. It is hoped that the results of this community service will provide benefits, namely by providing understanding and skills in using social media so that they can be used for marketing promotions in a wider range. By providing understanding and skills in using social media to MSME owners, it is hoped that social media can be utilized so that marketing can be broader and more people can get to know MSME products.